An evaluation of the strengths and weaknesses of South Africa’s corporate rescue regime as a potential benchmark for Uganda - Waiswa, Abudu Sallam (University of South Africa, 2022)
This thesis evaluates the strengths and weaknesses of the legal framework on corporate rescue in South Africa and Uganda. Although corporate rescue was initially not one of the objectives of insolvency law, it has now become the focus of modern insolvency law. South Africa became the first country to recognise the need to create a legal framework for rehabilitating financially distressed companies when it incorporated judicial management in the Companies Act of 1926. Judicial management was, however, not successful as a corporate rescue procedure. The South African policy makers however continued to explore ways through which financially distressed but viable companies could be saved from collapsing. This culminated into the introduction of business rescue in Chapter 6 of the Companies Act 71 of 2008. The study presents a detailed analysis of the strengths and weaknesses of the South African business rescue framework. It posits that unlike the Ugandan system, the South Africa legal regime reflects the principles of a modern and effective corporate rescue system. Whereas the government of Uganda attempted to embrace corporate rescue through the introduction of administration in the Insolvency Act 2011, the law is devoid of the internationally recognised features of a modern and effective business rescue framework. Administration has remained a white elephant in Uganda’s insolvency system, with liquidation continuing to be the predominant procedure used by both creditors and financially distressed companies. It is recommended that Uganda’s policy makers should benchmark the South African system to reform Uganda’s corporate rescue framework. This thesis is based on the law as at 31st of May 2022, found in the sources available in South Africa and Uganda.
Keywords: Bankruptcy; Business rescue; Corporate insolvency; Corporate insolvency law; Corporate reorganizations; Corporate rescue; Insolvency; Judicial management; Provisional administration; Rescue finance; South Africa; Uganda